Pengaruh Model Cooperative Learning Type Snowball Throwing Terhadap Kemampuan Pemahaman Matematis Siswa Sekolah Dasar - Andriyani, Lisa; Astriani, Linda (Jurnal PEKA (Pendidikan Matematika), 2026)
Mathematical understanding is a key skill that elementary students need in order to grasp concepts and solve problems, especially in fraction material, which often becomes a source of difficulty and misconceptions. This research seeks to determine the influence of the Cooperative Learning model-specifically the Snowball Throwing type-on students’ mathematical understanding abilities. The study was carried out at SDN Pondok Pinang 01 during the 2024/2025 academic year using a quasi-experimental approach with a Posttest Only Control Group Design. The participants consisted of 58 fourth-grade students selected through purposive sampling, divided equally into an experimental group and a control group. The instrument used was a set of 10 essay questions aimed at assessing students’ comprehension of fraction concepts. Data analysis through the Independent Sample T-Test revealed a significant difference between the two groups, with the experimental class demonstrating a higher average score. These results indicate that the Snowball Throwing model positively contributes to enhancing elementary students’ mathematical understanding